The Effect of the Problem Based Learning using STEM Approach on Higher Order Thinking Skills and Learning Activities in Junior High School Students - Alfina Dwi Wahyuningtyas; Pramudya Dwi Aristya Putra*; Ulin Nuha (Universitas Syiah Kuala, 2023)
Higher-order thinking skills (HOTS) are one of the skills that must be possessed by students in facing the demands of the 21st century. However, Indonesian students' HOTS currently tends to be low. The purpose of this study was to determine the effect of the PBL using STEM approach on students’ HOTS and learning activities. The sample of this study was 48 Junior High students who separated in two clases (experiment and control group). All the students were of 8th grade in SMPN 2 Ajung with a non-equivalent control group design. HOTS data was obtained by giving a pretest and posttest with 10 multiple choice questions. Furthermore, the learning activities was observed via activies observation protocol during the learning process. The application of the PBL using STEM approach was quite effective in the experimental class with a posttest average of 85. This was confirmed by the paired sample test of 0.001 0.05 which could be concluded that the PBL uisng STEM approach had a significant effect on HOTS and learning activities. This finding is an alternative integrative model innovation between PBL and STEM based on students' skill levels